Current Trends in Chronic Non-Communicable Disease Management: A Bibliometric Analysis of the Past Two Decades - Xiao S; Dong Y; Xia Y; Xu H; Weng F; Liang G; Yi Q; Ai C (Journal of Multidisciplinary Healthcare)
Shiyong Xiao,1,* Yongqi Dong,2,* Yuan Xia,3 Hongyan Xu,4 Falin Weng,5 Guohong Liang,6 Qianzhang Yi,7 Chengming Ai8 1Department of Clinical Nutrition, Wushan County People’s Hospital of Chongqing, Chongqing, 404700, People’s Republic of China; 2Department of Gastroenterology, Wushan County People’s Hospital of Chongqing, Chongqing, People’s Republic of China; 3Department of General Practice, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 4Department of Infectious Diseases, the Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 5Department of Geriatric Medicine, Wushan County People’s Hospital of Chongqing, Chongqing, People’s Republic of China; 6Department of Oncology, Wushan County People’s Hospital of Chongqing, Chongqing, People’s Republic of China; 7Department of Radiology, Wushan County People’s Hospital of Chongqing, Chongqing, People’s Republic of China; 8Department of Physical Examination Center, Wushan County People’s Hospital of Chongqing, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chengming Ai, Department of Physical Examination Center, Wushan County People’s Hospital of Chongqing, Wushan County, Chongqing, People’s Republic of China, Email 790298077@qq.comBackground: In recent years, there has been a growing focus on chronic non-communicable diseases (NCD) and their impact on personal and social health. Effective management of NCD is essential for their prevention and treatment. This study aims to utilize bibliometric methods to analyze and summarize the current development and emerging trends in NCD management.Methods: A literature search and screening were conducted on the Web of Science Core Collection database from January 1, 2004, to December 31, 2023. VOSviewer and Citespace software was performed to examine publication volume, authors, institutions, countries, journals, citation frequencies, keywords, clustering, and burst terms, and to create a visual map.Results: A total of 996 valid publications from 464 journals were included in the study. The number of publications exhibited a gradual growth trend over the years. The United States was the most productive and influential country, contributing the highest proportion of both publications and total citations. BMC Health Services Research, Toronto University, and Marshall, Bruce C. were identified as the most productive journal, institution, and author, respectively. Further analysis of keyword co-occurrence and burst detection revealed that the most prevalent keywords were “improving primary care” and “integrated care”.Conclusion: This bibliometric analysis provides a comprehensive overview of the current status and trends in NCD management over the past two decades, providing valuable insights for future research directions. It indicates a potential shift towards enhancing primary healthy care, integrated care, and digital health.Keywords: non-communicable diseases, bibliometric analysis, management, primary health care, integrated care, digital health